(untitled) (Journal of Nepal Paediatric Society, 2016)
Introduction: Pneumonia remains a significant health problem in India with significant morbidity and mortality. Objectives of this study were to identifying an effective nutritional agent that reduces the need for antibiotics, duration of pneumonia and length of hospitalization would be highly cost-beneficial. Material and Methods: This was a hospital-based case-control study: A total of 100 children including 50 cases and 50 controls, aged 2–60 months, were enrolled. Case definition of severe ALRI as given by the World Health Organization was used for cases. Controls were healthy children attending outpatients’ service for immunization or admitted for minor ailments other than ALRTI. Results: Mean 25(OH)D concentrations in children of the study group were lower than those of the control group (20.431 ng/mL vs. 27.67 ng/mL; p = 0.035). Factors significantly associated with decreased risk of ALRTI in univariate analysis were: exclusive breastfeeding in the first 6 months (cases 13/50 (26%), controls 42/50 (84%); p=0.000); adequate exposure to sunlight (cases 14/50 (28%), controls 42/50 (84%); P=0.000); and serum 25OHD3 <20 ng/ml (cases 28/50 (56%), controls 0/50 (0%); p=.000). Multivariate logistic model indicated that severe vitamin D deficiency (OR=NA), exclusive breast feeding (OR=.174); 95% CI (.061- .521; p=.002) and adequate sunlight exposure (OR=.179) ;95%CI (.062-.519); p=.002) were significant independent predictive risk factors for ALRTI among the children between 2 months – 5 years of age (all p<0.05). Conclusion: Severe vitamin D deficiency (<20ng/ml), nonexclusive breastfeeding in the first six months of life, inadequate sun exposure were significant risk factors for ALRTI in Indian children. J Nepal Paediatr Soc 2016;36(1):14-18